ANALISIS TERHADAP PEMBAGIAN WARISAN ANTARA ANAK LAKI-LAKI DAN NAK PEREMPUAN : Perspektif Hukum Islam - Muhlisina (STAI YAPIS Takalar, 2021)
Islamic inheritance law is a law that regulates everything related to thetransfer of rights and obligations of a person's assets after death to his heirs. Thus, inIslamic law there are three interrelated elements, namely: heirs, inheritance andheirs. Islamic law has explained the provisions or matters relating to thearrangement of the distribution of inheritance with very fair rules in accordance withthe provisions of the Qur'an and the Compilation of Islamic Law (KHI), in thisIslamic inheritance law rule has been determined the share of each heir, both maleand female. both men and women. However, based on reality, many people who areMuslims consider the division of inheritance between sons and daughters in Islamiclaw with a ratio of 2:1 not fair.